2004 IEEE 35th Annual Power Electronics Specialists Conference (IEEE Cat. No.04CH37551)
DOI: 10.1109/pesc.2004.1355530
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of stranded-wire windings and comparison with litz wire on the basis of cost and loss

Abstract: Abstract-Stranded wire with uninsulated strands has been proposed as a low-cost alternative to litz wire. In this paper, we develop a method to optimize stranded-wire designs on the basis of cost and loss, and compare the results to optimized litz-wire designs. A simply calculated parameter is shown to be useful to predict when each type of wire is preferred. A method to extend both loss prediction and optimization for arbitrary geometries and waveforms is also introduced.Deliberate oxidation of strands is pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…We have observed that the tinned cable has considerably higher AC resistance, which is caused by current concentration at conductor surface (tin) at higher frequencies. It is also observed that the improvement with the Litz wire inductor over the normal stranded copper is less than might have been expected, in particular at frequency range of interest 500-2000Hz, since the uninsulated stranded wire offers some benefit at reducing the AC losses as discussed in [13]. Note that the values shown in Table IV represents a single inductor in isolation.…”
Section: High Power High Frequency Inductors and Capacitormentioning
confidence: 92%
“…We have observed that the tinned cable has considerably higher AC resistance, which is caused by current concentration at conductor surface (tin) at higher frequencies. It is also observed that the improvement with the Litz wire inductor over the normal stranded copper is less than might have been expected, in particular at frequency range of interest 500-2000Hz, since the uninsulated stranded wire offers some benefit at reducing the AC losses as discussed in [13]. Note that the values shown in Table IV represents a single inductor in isolation.…”
Section: High Power High Frequency Inductors and Capacitormentioning
confidence: 92%
“…where R dc is the dc resistance of the wire, δ is the skin-depth, r s is the strand radius [24][25][26], ρ is the resistivity of copper, l w is the length of the wire, and A w is the effective copper area of the wire. The parameters of the litz wire, from Pack Litz Wire, considered in the design analysis are shown in Table 1 [27].…”
Section: Electrical Modelmentioning
confidence: 99%
“…The ambient temperature is assumed to be equal to 20 • C. Furthermore, the axial height of the air gap that separates the primary and secondary core (h ag ) and load resistance are fixed to 0.5 mm and 23.5 Ω, respectively. The optimization problem, shown in (26), is solved by applying the parametric search method. The frequency is varied from 50 kHz up to and including 1 MHz in incremental steps of 25 kHz.…”
Section: Pot Core Design Optimizationmentioning
confidence: 99%
“…The dc resistance is calculated using [10]. A low ac resistance is achieved by using Litz wire, designed using [11,12]. The calculation of the mutual inductance between coils is based on the mutual inductance between two circular filaments, arbitrarily positioned in space [13].…”
Section: Analysis and Designmentioning
confidence: 99%